2020
DOI: 10.1029/2019ms001816
|View full text |Cite
|
Sign up to set email alerts
|

Present‐Day and Historical Aerosol and Ozone Characteristics in CNRM CMIP6 Simulations

Abstract: Characteristics and radiative forcing of the aerosol and ozone fields of two configurations of the Centre National de Recherches Météoroglogiques (CNRM) and Cerfacs climate model are analyzed over the historical period (1850-2014), using several Coupled Model Intercomparison Project 6 (CMIP6) simulations. CNRM-CM6-1 is the atmosphere-ocean general circulation model including prescribed aerosols and a linear stratospheric ozone scheme, while the Earth System Model CNRM-ESM2-1 has interactive tropospheric aeroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 116 publications
0
24
0
Order By: Relevance
“…The UKESM1 model includes an interactive stratosphere-troposphere gas-phase chemistry scheme (Archibald et al, 2020) using the UK Chemistry and Aerosol (UKCA; Morgenstern et al, 2009;O'Connor et al, 2014) model. The UKCA aerosol scheme, called GLOMAP mode is two-moment simulation of tropospheric black carbon, organic carbon, SO 4 and sea salt.…”
Section: Modelsmentioning
confidence: 99%
“…The UKESM1 model includes an interactive stratosphere-troposphere gas-phase chemistry scheme (Archibald et al, 2020) using the UK Chemistry and Aerosol (UKCA; Morgenstern et al, 2009;O'Connor et al, 2014) model. The UKCA aerosol scheme, called GLOMAP mode is two-moment simulation of tropospheric black carbon, organic carbon, SO 4 and sea salt.…”
Section: Modelsmentioning
confidence: 99%
“…Previous studies using long-term data since the 1980s, mainly over Europe and North America, have found that global models are able to reproduce the observed multi-decadal changes in aerosols relatively well (Pozzoli et al, 2011;Leibensperger et al, 2012;Tørseth et al, 2012;Chin et al, 2014;Turnock et al, 2015;Aas et al, 2019). More recently, global composition models, including some CMIP6 models, were shown to be able to reproduce the observed changes in AOD, sulphate and particulate matter over the last 2 decades (Mortier et al, 2020). The ability of global composition models to reproduce historical changes in aerosols provides a degree of confidence in the future projections under the CMIP6 scenarios.…”
Section: Surface Pm 25mentioning
confidence: 99%
“…From regional air quality to global climate this database of ESM outputs will enable advances in our understanding of how the climate system responds to short-term perturbations. (Michou et al, 2020) Interactive above 560 hPa, prescribed below ( Michou et al, 2020) interactive E3SM-1-1 Burrows et al # number of aerosol species, and name/description of aerosol sub-model * These models used the first version of the ozone fields that had a small bug in the vertical interpolation of the ozone perturbation, stretching the ozone perturbation to too high altitudes. The models weres not able to re-run the model simulations with the corrected ozone fields.…”
Section: Accepted Articlementioning
confidence: 99%